Advances in post-translational modifications of proteins and cancer immunotherapy - Li, Yanqing; Zhang, Runfang; Hei, Hu (Frontiers in Immunology, 2023)
Protein post-translational modification (PTM) is a regulatory mechanism for protein activity modulation, localization, expression, and interactions with other cellular molecules. It involves the addition or removal of specific chemical groups on the amino acid residues of proteins. Its common forms include phosphorylation, ubiquitylation, methylation, and acetylation. Emerging research has highlighted lactylation, succinylation, and glycosylation. PTMs are involved in vital biological processes. The occurrence and development of diseases depends on protein abundance and is regulated by various PTMs. In addition, advancements in tumor immunotherapy have revealed that protein PTM is also involved in the proliferation, activation, and metabolic reprogramming of immune cells in tumor microenvironment. These PTMs play an important role in tumor immunotherapy. In this review, we comprehensively summarize the role of several types of PTMs in tumor immunotherapy. This review could provide new insights and future research directions for tumor immunotherapy.